Exploring gender and society - Ecoben, Wenceslao B. (Mandaluyong City, 2023)
Gender is an important element in a growing society like ours. We may not be the leading movers for gender awareness yet the Philippines is not far behind. Gender has something to do with social development. The common stereotype is - men are leaders and leaders are social movers. Men are akin to social development. Therefore, social progress is man's preoccupation. What if, the stereotype may no longer hold true and women are also social movers for sustainable development in today's world.
Keywords: Gender identity; Gender identity-Social aspects; Sex diffrerences-Social aspects